Development Time Signal Violation Learning Video for Basic Basketball Referee - Raditya Pratama; Himawan Wismanadi; Abdul Rachman Syam Tuasikal (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
Time signal violation material is a basic material that must be mastered by a basketball referee. This research includes the type of research and development. The results of this research and development is a learning tool basketball refereeing time signal violation tool packed in a dvd video. Results of small group testing of the product obtained a feasibility percentage of 83.33%. While the results of large group trials obtained a percentage of eligibility of 88.97%.